2013
DOI: 10.3897/zookeys.356.6481
|View full text |Cite
|
Sign up to set email alerts
|

The “Taygetis ypthima species group” (Lepidoptera, Nymphalidae, Satyrinae): taxonomy, variation and description of a new species

Abstract: A new species of Taygetis Hübner, [1819] (Lepidoptera, Nymphalidae, Satyrinae) from southeastern Brazil is described: Taygetis drogoni sp. n. In addition, T. servius Weymer, 1910 and T. fulginia d’Almeida, 1922 are resurrected from synonymy and a taxonomic discussion on the species T. ypthima Hübner, [1821] and T. rectifascia Weymer, 1907 is provided. A dichotomous key for the species is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
(34 reference statements)
0
17
0
2
Order By: Relevance
“…The genera Forsterinaria , Parataygetis and the ‘ Taygetis ypthima species group’ of Siewert et al . () (new genus ypthima + new genus rectifascia ) were recovered as monophyletic. Although the genus Taygetina was strongly supported by molecular data (Matos‐Maraví et al ., ), it emerged as polyphyletic here, possibly due to the marked morphological differences among the species.…”
Section: Discussionmentioning
confidence: 98%
“…The genera Forsterinaria , Parataygetis and the ‘ Taygetis ypthima species group’ of Siewert et al . () (new genus ypthima + new genus rectifascia ) were recovered as monophyletic. Although the genus Taygetina was strongly supported by molecular data (Matos‐Maraví et al ., ), it emerged as polyphyletic here, possibly due to the marked morphological differences among the species.…”
Section: Discussionmentioning
confidence: 98%
“…In Satyrinae, for example, recent studies have demonstrated the usefulness of the examination of female genitalia to identification and delimitation of species (i.e. Pyrcz 2010; Siewert et al 2014;Penz et al 2014). In "Pierella lamia species group", female genitalia are completely distinct each other concerning their total size, structures shape and signa position, while the male genitalia of almost all species of these group (except P. boliviana) is homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24,[41][42][43][44][45]), and (2) cryptic species eventually distinguished by subtle external characters and/or morphology of genitalia (e.g. [20,25,46,47] this paper). The increasing use of molecular data such as the DNA barcodes has increased the identification of those in the second group (cryptic species), helping to uncover a high hidden biodiversity in Euptychiina.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences were analyzed with the program FinchTV v. 1.4.0 (Geospiza, PerkinElmer Inc., Waltham, MA), and posteriorly aligned using BioEdit v. 7.2.4 (Tom Hall 2013, available at http:// www.mbio.ncsu.edu/bioedit/bioedit.html#downloads) with GenBank sequences (Yph_sp, CP08-88; CP12-03; MAL-04257; 07-SRNP-100018). [20] The final matrix comprised 44 sequences from 16 Yphthimoides species ( Table 1).…”
Section: Genetic Distance and Relationship Analysismentioning
confidence: 99%
See 1 more Smart Citation